Genesis and Operational Characteristics of the Slovenian War of Independence in Prekmurje and Prlekija Region 30 Years Ago - Šteiner, Alojz (Anali PAZU HD, 2022)
Thirty years after the end of the military conflicts in Slovenia, from 27 June to 7 July 1991, an exceptional number of works were created describing the activities of Slovenian defence structures in Slovenian War of Independence. Also works with views from the opposite side were created and published. Most of the works are commemorative records and testimonials, some are historical works with depictions and analyses of events or even just the presentation of documents. Scientific-research and military-expert analyses are a rarity. The paper shows the findings from the analysis of the characteristics of independence and military action in the case of Prekmurje and Prlekija. In the case of the province along the Mura region it is precisely that the characteristics of the operation of the Yugoslav People’s Army are eloquently shown, as well as the specifics of the countering activities of the Slovenian Defence Forces. From this I conclude on the genesis and operational characteristics of the war in the Republic of Slovenia and the intentions to forcibly prevent Slovenian independence. These indicators are in Pomurje region more recognizable than elsewhere in Slovenia.